Phytochemical analysis, antioxidant, antibacterial and antidiarrheal activities of Limnophila repens - Afroza Akter; Mohammad Anwarul Basher; Roni Roy; Sharmin Sultana; A F M Shahid Ud Daula (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
The study was carried out to determine the phytochemical content, antioxidant, antibacterial and antidiarrheal activity of methanolic extract of whole plant of Limnophila repens. The total phenolic, flavonoids, flavonols, tannins, β-carotene, lycopene, chlorophyll-α, and chlorophyll-β contents were found to be 65.21 ± 0.004 mg GAE/g , 44.83 ± 0.003 mg QE/g , 17.21 ± 0.002 mg QE/g, 56.27 ± 0.002 mg GAE/g , 1.32 ± 0.01 µg/g, 0.93 ± 0.012 µg/g, 11.85 ± 0.04 mg/g and 9.69 ± 0.037 mg/g, respectively. In vitro antioxidant potential of L. repens was assessed using various methods like by 2,2-diphenyl-1 picrylhydrazyl (DPPH), hydroxyl radical scavenging assay, reducing power assay, FRAP assay and thiobarbituric acid assay. IC50 values of the aforesaid tests were found to be 2.33 mg/ml, 442.31 µg/ml, 374 µg/ml, 55.09 µg/ml, and 4.30 mg/ml, respectively. The total antioxidant capacity was observed 140.7 ± 0.004 mg/g AAE. Aantibacterial activity of the methanolic extracts of whole plant of L. repens was evaluated using the disk diffusion method. The plant extract didn’t show any activity against Gram-positive (except Staphylococcus aureus) and Gram-negative bacteria. Finally, castor oil induced method was conducted to investigate the antidiarrheal activity of L. repens. At the dose of 400 mg/kg, the plant extract (35.62% inhibition of diarrhea) exhibited stronger effect compared to standard drug, loperamide (27.4% inhibition of diarrhea).